Stephen D. Bowd, Renaissance Mass Murder: Civilians and Soldiers during the Italian Wars - Papanikolaou, Elli (The Historical Review/La Revue Historique, 2021)
Review of: Stephen D. Bowd, Renaissance Mass Murder: Civilians and Soldiers during the Italian Wars